The Influence of Product Quality and Electronic Word of Mouth on Purchase Decisions with Buying Interest as Mediation - Fero Fairuz Firdaus Ananta; Nur Asnawi (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This study aims to analyze the influence of product quality and Electronic Word of Mouth (e-WOM) on the purchase decision of Somethinc cosmetics in Malang City, with buying interest as a mediating variable. Cosmetics have become an essential product for many consumers, especially women, who are looking for high-quality products to improve their appearance and confidence. In this context, e-WOM plays a significant role in shaping consumer perceptions and influencing purchasing decisions. The research method used is quantitative with a survey approach, involving Somethinc consumer respondents in Malang City. Data were collected through questionnaires and analyzed using regression analysis techniques using Smart-PLS 4. The results showed that e-WOM had a significant positive influence on buying interest, which in turn had an impact on purchasing decisions, product quality did not directly affect buying interest, then directly affected purchasing decisions but not significant for Somethinc cosmetics. These findings provide important insights for marketers in formulating effective strategies to increase sales of cosmetic products.